How Transformational Leadership and Organizational Culture Affect Health Worker Performance? A Literature Review - Asrawijaya, Prasasta; Hidayah, Nur (Universitas Aisyah Pringsewu, 2022)
Health personnel must maintain their performance in delivering health care due to their numerous responsibilities. Health care professionals' performance is affected by transformational leadership and organizational culture. Identify and summarize studies on the impact of transformational leadership and organizational culture on the performance of hospitalized health professionals. This study is a literature review that was conducted by searching publications published between 2011 and 2021 in the electronic databases Pubmed, Emerald, Google Scholar, JMMR, and Scopus that met the inclusion criteria. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance is used in the review process. Eleven papers demonstrate the impact of transformational leadership on health worker performance, while eleven publications demonstrate the impact of corporate culture on health worker performance. Implication, transformational leadership and organizational culture have a large and favorable impact on health professionals' performance. will raise the standard of healthcare services. Abstrak: Banyaknya tugas dari tenaga kesehatan menjadikan seorang tenaga kesehatan perlu menjaga kinerjanya dalam memberikan pelayanan kesehatan. Kepemimpinan transformasional dan budaya organisasi menjadi faktor dalam menjaga dan meningkatkan kinerja tenaga kesetahan. Untuk mengidentifikasi dan mensintesis penelitian tentang pengaruh kepemimpinan transformasional dan budaya organisasi terhadap kinerja tenaga kesehatan di rumah sakit. Penelitian ini merupakan Literature review dengan penelusuran artikel melalui database elektronik Pubmed, Emerald, Google Scholar, JMMR dan Scopus yang diterbitkan dari tahun 2011-2021 dan memenuhi kriteria inklusi. Proses review menggunakan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Sebelas artikel menunjukan pengaruh kepemimpinan transformasional terhadap kinerja tenaga kesehatan dan Sebelas artikel menunjukan pengaruh budaya organisasi terhadap kinerja tenaga kesehatan Artinya, kepemimpinan transformasional dan budaya organisasi memiliki pengaruh yang signifikan dan positif terhadap kinerja tenaga kesehatan. Implikasinya, rumah sakit yang dapat mempetimbangkan kepemimpinan transformasional dan budaya organisasi akan dapat meningkatkan kualitas pelayanan rumah sakitnya.